EFFECT OF EFFECTIVENESS AUDIT COMMITTEE, INTERNAL AUDIT AND QUALITY OF AUDIT ON PROFIT MANAGEMENT - Fristy Dwi Andita Salama; Murdiyati Dewi (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
The importance of Earnings Management for management is to determine the direction of Stakeholder decisions, it is very important, but Stakeholders will receive a bad impact from Earnings Management because of the number game practice carried out by management such as not obtaining invalid and adequate data so that in determining action they cannot take the right things. should be for the company (Sulistyanto, 2008). When earnings management actions are revealed, this has another effect, namely bad management which will have a major impact on the company, consequently reducing the trust of external parties to the company's managers (Berger & DeYoung, 1997). So, it is advisable to take several steps to strengthen the quality of corporate governance, including the effectiveness of the audit committee, internal audit and external audit practices (Yassin & Nelson, 2012)